Design and Research of the Improved Structure of Tire Coupling - Yang Fuqin; Jiang Dianbing; Li Songmei; Yang Weikun (Jixie chuandong)
Due to the larger radial dimension of the tire coupling,the additional axial force making the bearing load is increased and life is reduced,in order to solve this problem,using TRIZ to analyze the radial dimension problem of the tire coupling and find the solutions. The problem of tire coupling is solved by the tire ring and trapezoidal timing belt nested to form a new structure. Through the ANSYS finite element analysis,the rationality of its structure is verified,which is hoped to expand its application.